Analysis of the Urgency of Sharia Fatwas on Zakat Management for Renewable Energy An Islamic Political Perspective in the Context of the Climate Crisis - Ahmad Alimuddin; Islamul Haq; Zulfahmi AR (International Journal of Sharia and Law, 2025)
This study aims to analyze the role and urgency of sharia fatwas in legitimizing and operationalizing zakat as a financing instrument for renewable energy projects, viewed through Islamic political thought in the context of the global climate crisis. Employing a qualitative approach, the research utilizes document analysis of fatwas (e.g., MUI Fatwa No. 15/2017 and Malaysian zakat fatwas), interviews with representatives from zakat institutions (Baznas and State Zakat Centers), and case studies of renewable energy projects in Indonesia and Malaysia. The findings reveal that sharia fatwas provide robust legal legitimacy for channeling zakat into green projects like solar power plants (PLTS) and biomass initiatives, aligning with maqasid sharia’s hifzhul bi’ah (environmental preservation) and supporting global climate goals, such as the 2050 net-zero emissions target. Despite challenges like low sharia literacy and limited fund scales, zakat demonstrates significant potential to support Sustainable Development Goals (SDGs) 7 and 13, fostering socio-economic benefits for mustahik through clean energy access and green job creation. The study concludes that sharia fatwas and green zakat serve as innovative tools to bridge Islamic values with global environmental policies, enhancing sustainability. Academically, it contributes by developing the concept of green zakat, filling a literature gap in integrating zakat with renewable energy financing, and offering a framework for aligning sharia-based finance with sustainable development.